(untitled) (Economics and region, 2018)
Notions of decisions making support, informational support of making managerial decisions and informational support of making strategic managerial decisions are considered. Demands to model of signatory evaluation of enterprise activity results are suggested, characteristics of such model are shown and comparative analysis of such model with existing models in strategic analysis is made. List of indicators to build model of signatory evaluation of enterprise activity results is formed. Such indicators are divided by management levels. Examples of binary analytical and managerial matrixes based on suggested indicators are built.